SPATIAL AND TEMPORAL VARIATIONS IN THE 13C / 12C AND 15N / 14N RATIOS OF MAMMOTH HAIRS: PALAEODIET AND PALAEOCLIMATIC IMPLICATIONS - Iacumin P.; Davanzo S.; Nikolaev V. (My University, 2006)
Four sets of C and N stable isotope analyses carried out on mammoth hairs of different radiocarbon age from four different sites in northern Siberia are reported here. Another set of analyses from the same region, published elsewhere, is reported for comparison. The analyses were performed on small increments along the length of the hairs providing information about short-(seasonal) and long-term (before and after the Last Glacial maximum) diet variation and, hence, about the environment in which the mammoths lived. The mean δ13C and δ15N values for the four sites range between - 24.1‰ and - 20.9‰ and between 5.8‰ and 9.6‰, respectively. Both the δ13C and δ15N signals increment towards east when samples from the same age are considered. Hair δ15N correlates well with the current amount of precipitation independently of the radiocarbon age of the sample. This could mean that during the periods considered this environmental parameter did not change significantly in the studied sites. Hair δ13C appears to be affected by a different environmental factor that, in this case, varies in function of the radiocarbon age of the samples. This factor could be the CO2 atmospheric content that, as is well know, varies across a glacial cycle depending on temperature. The isotope patterns obtained from each set of samples exhibit roughly sinusoidal oscillations of the δ13C and δ15N values. These oscillations have been attributed to seasonal changes in the isotope values of the mammoth's diet due to plant adaptation to the different seasonal environmental conditions or to the different seasonal plant type availability. A direct physiological effect on the hair δ15N values can also be considered. This study strongly supports the possibility of using hair δ13C and δ15N signals as indicators of geographical and temporal variation in plant isotope composition and, ultimately, as indicators of palaeoclimate changes. © 2006 Elsevier B.V. All rights reserved.
Keywords: CARBON ISOTOPES; MAMMOTH HAIR; NITROGEN ISOTOPES; NORTHERN SIBERIA; PALAEODIET; PALAEOENVIROMENT